Translational Regenerative Therapies for Chronic Spinal Cord Injury - Dalamagkas, Kyriakos (Int J Mol Sci, 2018)
Spinal cord injury is a chronic and debilitating neurological condition that is currently being managed symptomatically with no real therapeutic strategies available. Even though there is no consensus on the best time to start interventions, the chronic phase is definitely the most stable target in order to determine whether a therapy can effectively restore neurological function. The advancements of nanoscience and stem cell technology, combined with the powerful, novel neuroimaging modalities that have arisen can now accelerate the path of promising novel therapeutic strategies from bench to bedside. Several types of stem cells have reached up to clinical trials phase II, including adult neural stem cells, human spinal cord stem cells, olfactory ensheathing cells, autologous Schwann cells, umbilical cord blood-derived mononuclear cells, adult mesenchymal cells, and autologous bone-marrow-derived stem cells. There also have been combinations of different molecular therapies; these have been either alone or combined with supportive scaffolds with nanostructures to facilitate favorable cell–material interactions. The results already show promise but it will take some coordinated actions in order to develop a proper step-by-step approach to solve impactful problems with neural repair.